Market-Oriented Fundraising in Government Zakat Institutions: Evidence from Central Java, Indonesia - Alam, Azhar; Jannah, Nur; Nisa', Eka Lutfia Khoirun; Isman (Velocity: Journal of Sharia Finance and Banking, 2025)
This study examines how government zakat institutions, specifically BAZNAS Solo, Boyolali, and Sragen, employ market-oriented fundraising strategies to enhance muzakki participation and trust in zakat distribution. Using a qualitative descriptive approach, data were collected through in-depth interviews with 10 BAZNAS officers and 10 muzakki, supplemented by relevant literature on market-oriented fundraising. The qualitative method was selected to capture the nuanced perspectives and contextual factors influencing the effectiveness of these strategies, which may not be fully understood through quantitative measures alone. The findings reveal that all three BAZNAS utilize digital applications (such as Simba lite and Muzakki Corner), community training, targeted socialization, and partnerships with online marketplaces and local organizations to increase zakat collection and public trust. However, challenges persist, including limited digital literacy among some donors and the need for improved transparency and accountability. These results highlight the importance of adaptive fundraising strategies for government zakat institutions and suggest that future research could benefit from a mixed-methods approach to evaluate the impact and scalability of these innovations.